Preoperative vaginal estrogen and midurethral sling exposure: a retrospective cohort study. Issue 3 (March 2016) - Cadish, Lauren; West, Elizabeth; Sisto, Jessica; Longoria, Teresa; Bebchuk, Judith; Whitcomb, Emily
Abstract Introduction and hypothesis We evaluated whether the use of estrogen vaginally prior to synthetic midurethral sling insertion mediates the risk of mesh exposure. A secondary aim was to evaluate other factors that may be associated with mesh exposure. Methods We performed a retrospective cohort study of patients undergoing midurethral sling insertion from January to December 2010 within the Southern California Permanente Medical Group. Women who used estrogen vaginally prior to surgery were classified as those who filled a prescription between 1 and 45 days before surgery or whose medical records indicated its use at the time of preoperative evaluation. Logistic regression analysis was used to calculate odds ratios (OR) and 95 % confidence intervals (CI) for factors associated with mesh exposure while controlling for confounding variables. Results A total of 1544 patients met inclusion criteria, of whom 248 (16.1 %) used estrogen vaginally prior to surgery. Mean age was 53.7 years (range 27–89). Thirty-seven (2.4 %) women were diagnosed with mesh exposure, of whom 19 underwent surgical reoperation. In multivariate logistic regression analysis, preoperative use of estrogen vaginally was not associated with the risk of mesh exposure (OR 0.79, CI 0.26–2.38, p = 0.67). Age, body mass index, menopausal status, use of hormone replacement therapy, smoking status, and diabetes were not associated with risk of mesh exposure. Conclusions Preoperative use of estrogen vaginally did not appear to mediate the risk of mesh exposure following midurethral sling placement in this cohort.